Histological evaluation of acetabular bone quality during revision hip arthroplasty. Issue 2 (December 2020) - Bistolfi, Alessandro; Linari, Alessandra; Aprato, Alessandro; Fusini, Federico; Cravero, Ester; Papotti, Mauro; Ferracini, Riccardo; Massè, Alessandro
Purpose: Aim of this study was to evaluate acetabular bone vitality during revision hip arthroplasty and to compare the bone quality between revision and primary acetabular arthroplasty. Methods: During primary and revision total hip arthroplasty surgeries, biopsies were taken from the acetabulum after reaming. The samples (osteochondral cylinders of approximately ⩽1 cm long and 3 mm thickness), after removing the mineral component, were cut longitudinally with a thickness section of 5 µm and colored with hematoxylin-eosin dichromic dye and then evaluated histologically by optical microscopy with 40× magnification. Preoperative radiographs were evaluated. Results: According to inclusion and exclusion criteria, 14 patients formed the revision group patients (mean age: 67.9 years, average time before revision 8.8 years, SD ± 7.06) and 5 patients formed the control primary group (mean age: 61.4 years). The bone quality of the revision group was generally poorer than the primary group, while similar vitality and bone quality has been found between septic and aseptic group. Variables such as age, gender and BMI did not significantly contribute to define bone quality classes. Conclusions: The study confirms the differences in quality and bone vitality between cases and controls and the necessity to find strategies to improve the osteointegrative processes in revision arthroplasties.